The Influence Of Halal Labeling And Price On Purchase Decisions Of Kropinka Products - Sa'bani, Ria; Munadi; Nuraini (STKIP MAJENANG, 2025)
The halal status and price of a product significantly impact purchasing decisions. For example, Kropinka. The products offered have received halal certification from the relevant authorities. On the other hand, Kropinka also has a price difference compared to commonly sold coffee in the market. However, the demand for Kropinka is very high, leading Kropinka farmers to state that they struggle to meet the demand due to the sometimes insufficient supply of Kropinka. This situation makes Kropinka a suitable subject for research. The research methodology employed in this study is a quantitative method. The quantitative research method involves a specific population or sample. The data collected utilize research instruments and data analysis employs numerical (statistical) methods aimed at hypothesis testing applied to examine significance and hypothesis results. The review of the t-statistic shows 1.96, indicating that H0 is rejected. For the probability value, observing the p-value of 0.05, H0 is rejected. Thus, it can be concluded from this research that Variables X1 and X2 have significant values due to the p-value of 0.05. Based on the results of the conducted study, the following conclusions can be drawn: 1. The halal label present on KROPINKA product packaging has a relationship and significantly influences the purchasing decision of KROPINKA products, as indicated by a significance level of 0.024 < 0.05. This evidence demonstrates that the presence of halal labeling on KROPINKA products provides a positive value that significantly impacts consumers' purchasing decisions. 2. The varied prices of KROPINKA products corresponding to the types of products have a relationship and significantly influence the purchasing decision, as indicated by a significance level of 0.000 < 0.05. This further proves that the price The diverse range of products from KROPINKA provides a positive value that has a significant opportunity to influence consumer purchasing decisions. Additionally, halal labeling and pricing have a relationship and simultaneously exert a significant influence on the purchasing decisions of KROPINKA products